Mrs. Wiens Kindergarten Class at Jackson Elementary School - Watkins, Howard::::::::: (1984)
Group photograph of students, parents and teacher; Devon Bleile-Kratzer front row in red shorts; Art Wille and Adam Watkins in third row far right; Christie Docker wearing red tie; Nancy Bleile in yellow top and teacher LeAnne Wiens on far right